2016
DOI: 10.1021/acsnano.6b06531
|View full text |Cite
|
Sign up to set email alerts
|

Molding Inkjetted Silver on Nanostructured Surfaces for High-Throughput Structural Color Printing

Abstract: Inkjet printing of silver ink has been widely used to print conductive patterns in flexible electronic devices, and the printed patterns are commonly known to be colorless. We demonstrate that by printing a single type of ordinary silver nanoparticle ink on top of a substrate patterned with polymer nanostructures, the printed silver is molded by the nanostructures and gains robust structural colors. The colors are tunable by varying the geometries of nanostructures, and a broad range of visual colors can be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…Different types of photonic crystals have been used for inkjet printing to create structural color patterns for applications in security and anticounterfeiting. [109][110][111][112][113] The inkjet printing of silver NP ink on exible substrates has shown great potential for printing conductive patterns for wearable electronic devices. Jiang et al 113 reported printing of silver nanoparticle (AgNP) ink on top of the patterned polymer nanostructures where the polymer nanostructures molded the printed silver and yielding into structural colors.…”
Section: Inkjet-printed Nanomaterials For Flexible Electronicsmentioning
confidence: 99%
“…Different types of photonic crystals have been used for inkjet printing to create structural color patterns for applications in security and anticounterfeiting. [109][110][111][112][113] The inkjet printing of silver NP ink on exible substrates has shown great potential for printing conductive patterns for wearable electronic devices. Jiang et al 113 reported printing of silver nanoparticle (AgNP) ink on top of the patterned polymer nanostructures where the polymer nanostructures molded the printed silver and yielding into structural colors.…”
Section: Inkjet-printed Nanomaterials For Flexible Electronicsmentioning
confidence: 99%
“…Owing to their photonic bandgaps, they exhibit structural colors (SCs) in the visible wavelength region . PCs have potential applications in low‐power reflective‐mode displays, media boards, and sensors because of their versatile tunability of SCs through the dielectric contrast, dimensions, and shapes of the structural elements. PCs have also been demonstrated as nonvolatile, high‐density information recording media for various emerging smart technologies .…”
Section: Introductionmentioning
confidence: 99%
“…Although colloidal lithography has been employed to produce SPR‐active nanostructures in a wide area, multicolor micropatterning requires complex and delicate deposition and etching processes . Recently, relatively simple and reproducible methods on multicolor pattering of SPR‐active nanostructures have been suggested . However, the color patterns are insensitive to the environmental condition as metal nanostructures are fully covered by a polymeric matrix, restricting their applications.…”
Section: Introductionmentioning
confidence: 99%